On the depletion and accretion timescales of cold gas in local early-type galaxies - Davis, T; Bureau, M (Oxford University Press, 2016)
We consider what can be learnt about the processes of gas accretion and depletion from the kinematic misalignment between the cold/warm gas and stars in local early-type galaxies. Using simple analytic arguments and a toy model of the processes involved, we show that the lack of objects with counter-rotating gas reservoirs strongly constrains the relaxation, depletion and accretion time-scales of gas in early-type galaxies. Standard values of the accretion rate, star-formation efficiency and relaxation rate are not simultaneously consistent with the observed distribution of kinematic misalignments. To reproduce that distribution, both fast gas depletion (tdep ≲ 108 yr; e.g. more efficient star formation) and fast gas destruction (e.g. by active galactic nucleus feedback) can be invoked, but both also require a high rate of gas-rich mergers (>1 Gyr−1). Alternatively, the relaxation of misaligned material could happen over very long time-scales (≃100 dynamical times or ≈1–5 Gyr). We explore the various physical processes that could lead to fast gas depletion and/or slow gas relaxation, and discuss the prospects of using kinematic misalignments to probe gas-rich accretion processes in the era of large integral-field spectroscopic surveys.